The microbiologist's guide to metaproteomics - Tim Van Den Bossche; Jean Armengaud; Dirk Benndorf; Jose Alfredo Blakeley‐Ruiz; Madita Brauer; Kai Cheng; Marybeth Creskey; Daniel Figeys; Lucia Grenga; Timothy J. Griffin; Céline Henry; Robert L. Hettich; et al. (iMeta)
Abstract Metaproteomics is an emerging approach for studying microbiomes, offering the ability to characterize proteins that underpin microbial functionality within diverse ecosystems. As the primary catalytic and structural components of microbiomes, proteins provide unique insights into the active processes and ecological roles of microbial communities. By integrating metaproteomics with other omics disciplines, researchers can gain a comprehensive understanding of microbial ecology, interactions, and functional dynamics. This review, developed by the Metaproteomics Initiative (www.metaproteomics.org), serves as a practical guide for both microbiome and proteomics researchers, presenting key principles, state‐of‐the‐art methodologies, and analytical workflows essential to metaproteomics. Topics covered include experimental design, sample preparation, mass spectrometry techniques, data analysis strategies, and statistical approaches.